Nomenclatural notes about the names in Amaranthaceae published by Roberto de Visiani - Iamonico, Duilio; Clementi, Moreno (Hacquetia, 2016)
The names in Amaranthaceae published by R. de Visiani are investigated. Amaranthus gangeticus var. cuspidatus is a nomen nudum and thus invalid according to Art. 38.1a of the ICN. Amaranthus hierichuntinus, Atriplex patula var. hastifolia, and Chenopodium album var. oblongum are lectotypified, respectively, on a specimen preserved at PAD, and illustrations by Scopoli and Vahl. We here propose to synonymyze the three names (new synonymies) respectively with Amaranthus graecizans subsp. graecizans, Atriplex patula subsp. patula, and the type subspecies of C. album. For nomenclatural purposes, also the name C. lanceolatum Willd. (heterotypic synonym of C. album subsp. album) is investigated and lectotypified, on a specimen preserved at B.